Non-linear association between CD4+ T-cell counts and mortality risk in people living with HIV: evidence from a 10-year cohort study - Sun, Ruohan; Jia, Huangchao; Kang, Qiujia; Ma, Yanmin; He, Zichen; Ma, Xiuxia; Yuan, Jun; Guo, Huijun; Xu, Qianlei; Jin, Yantao (Frontiers in Medicine, 2025)
BackgroundThe study aimed to investigate the dose–response association between CD4+ T-cell counts and mortality risk in people living with HIV (PLHIV).MethodsData on PLHIV who had a high prevalence of acquired immunodeficiency syndrome (AIDS) were retrospectively collected from the routine treatment database in Henan Province, China, covering the period from October 2003 to October 2021. We randomly selected 1,000 PLHIV from age groups 30, 40, 50, and 60 years who met the inclusion criteria as study participants. The Kaplan–Meier analysis, the Cox proportional hazards regression model, and the restricted cubic spline (RCS) model were employed to analyze the association between CD4+ T-cell counts and mortality risk in PLHIV.ResultsA total of 4,000 participants were enrolled in the study, with a follow-up period of 28,158 person-years. During this period, there were 941 (23.5%) deaths, resulting in a mortality rate of 3.34 per 100 person-years. The mean duration of follow-up was 6.77 ± 3.45 years, and the cumulative survival rate was 76.5%. The Cox proportional hazards regression model revealed that as the CD4+ T-cell count increased, the hazard ratio (HR) decreased. The results of the RCS model demonstrated a non-linear association between CD4+ T-cell counts and mortality risk in PLHIV, with cutoff values for each age group being 382, 332, 334, and 215 cells/μL. The non-linear curve indicated that the HR decreased as the CD4+ T-cell counts increased. However, once the CD4+ T-cell counts reached their respective cutoff values, the curve showing the reduction in mortality risk began to flatten.ConclusionThere was a non-linear association between CD4+ T-cell counts and mortality risk in PLHIV. Although the cutoff values vary across age groups, they consistently remain close to 350 cells/μL. Therefore, considering a threshold of CD4+ T-cell count <350 cells/μL across various age groups is crucial as a strategic approach to mitigate mortality rates among PLHIV.